Parallel Mesh Adaptive Techniques for Complex Flow Simulation: Geometry Conservation - Angelo Casagrande; Pénélope Leyland; Luca Formaggia (Modelling and Simulation in Engineering)
Dynamic mesh adaptation on unstructured grids, by localised refinement and derefinement, is a very efficient tool for enhancing solution accuracy and optimising computational time. One of the major drawbacks, however, resides in the projection of the new nodes created, during the refinement process, onto the boundary surfaces. This can be addressed by the introduction of a library capable of handling geometric properties given by a CAD (computer-aided design) description. This is of particular interest also to enhance the adaptation module when the mesh is being smoothed, and hence moved, to then reproject it onto the surface of the exact geometry.